Effects of airway pressure release ventilation on multi-organ injuries in severe acute respiratory distress syndrome pig models - Aijia Ma; Bo Wang; Jiangli Cheng; Meiling Dong; Yang Li; Canzheng Wei; Yongfang Zhou; Yang Xue; Hui Gao; Lican Zhao; Siyu Li; Yiwei Qin; et al. (BMC Pulmonary Medicine, 2022)
Abstract Background Extra-pulmonary multi-organ failure in patients with severe acute respiratory distress syndrome (ARDS) is a major cause of high mortality. Our purpose is to assess whether airway pressure release ventilation (APRV) causes more multi-organ damage than low tidal volume ventilation (LTV). Methods Twenty one pigs were randomized into control group (n = 3), ARDS group (n = 3), LTV group (n = 8) and APRV group (n = 7). Severe ARDS model was induced by repeated bronchial saline lavages. Pigs were ventilated and monitored continuously for 48 h. Respiratory data, hemodynamic data, serum inflammatory cytokines were collected throughout the study. Histological injury and apoptosis were assessed by two pathologists. Results After severe ARDS modeling, pigs in ARDS, LTV and APRV groups experienced significant hypoxemia and reduced lung static compliance (Cstat). Oxygenation recovered progressively after 16 h mechanical ventilation (MV) in LTV and APRV group. The results of the repeated measures ANOVA showed no statistical difference in the PaO2/FiO2 ratio between the APRV and LTV groups (p = 0.54). The Cstat showed a considerable improvement in APRV group with statistical significance (p < 0.01), which was significantly higher than in the LTV group since 16 h (p = 0.04). Histological injury scores showed a significantly lower injury score in the middle and lower lobes of the right lung in the APRV group compared to LTV (p middle = 0.04, p lower = 0.01), and no significant increase in injury scores for extra-pulmonary organs, including kidney (p = 0.10), small intestine (p = 1.0), liver (p = 0.14, p = 0.13) and heart (p = 0.20). There were no significant differences in serum inflammatory cytokines between the two groups. Conclusion In conclusion, in the experimental pig models of severe ARDS induced by repetitive saline lavage, APRV improved lung compliance with reduced lung injury of middle and lower lobes, and did not demonstrate more extra-pulmonary organ injuries as compared with LTV.